Workshop Media Pembelajaran Berbasis Teknologi Informasi Dalam Menghadapi Revolusi Industri 4.0 - T Heru Nurgiansah (Jurnal Pengabdian UntukMu NegeRI, 2021)
Abstract The Industrial Revolution 4.0 era required the use of internet media in various areas of life including the field of education. The purpose of this devotional activity is to equip educators and prospective educators to be able to create technology-based learning media such as the use of Power Point media to make learning activities more interesting. The methods of devotion used are lectures, two-way discussions, and direct practice for participants of activities. The results of this activity managed to make participants able to use information technology-based learning media that will be a provision in future teaching activities. Keywords: Learning Media, Information Technology, Industrial Revolution 4.0 Abstrak Era Revolusi Industri 4.0 mengharuskan penggunaan media internet dalam berbagai bidang kehidupan termasuk bidang pendidikan. Tujuan kegiatan pengabdian ini adalah untuk membekali para pendidik maupun calon pendidik agar mampu membuat media pembelajaran berbasis teknologi seperti penggunaan media Power Point agar kegiatan pembelajaran lebih menarik. Metode pengabdian yang digunakan adalah ceramah, diskusi dua arah, dan praktek langsung bagi peserta kegiatan. Hasil kegiatan ini berhasil membuat peserta mampu untuk menggunakan media pembelajaran berbasis teknologi informasi yang akan menjadi bekal dalam kegiatan mengajar kedepan. Kata Kunci: Media Pembelajaran, Teknologi Informasi, Revolusi Industri 4.0